Self-regulation and co-regulation in early childhood: development, assessment and supporting factors - Erdmann, Kim; Hertel, Silke (Metacognition and learning, 2019)
The development of self-regulation represents one of the hallmarks in early childhood. This special issue addresses important questions regarding the assessment and development of self-regulation, as well as influencing factors in early childhood: (1) How can self-regulation be assessed in early childhood? (2) How can parents support the development of self-regulation at this age? (3) How do parent and child beliefs contribute to the development of self-regulation in young children? Targeting the first question, Mulder et al., Metacognition and Learning (2019) explore the dynamics of self-control strategies during delay of gratification in two- and three-year-old children. Neale and Whitebread, Metacognition and Learning (2019) emphasize the second question by analysing the stability of maternal scaffolding across toys and time with 12 to 24 month old infants and its relation to effortful control. Gärtner et al., Metacognition and Learning, 13(3), 241-264 (2018) contribute to the second and third question with their work on the relation of parents’ self-efficacy beliefs and co-regulation behaviour to child inhibitory control in two-year-old toddlers. The third question is also addressed by Compagnoni et al., Metacognition and Learning (2019), who report on the validation of a self-report instrument for assessing mindsets in kindergartners and its relation to self-regulation. The commonalities and differences among the four papers, and their empirical and theoretical contributions to the rising field of self-regulation research in early childhood are discussed by Claire Hughes, Metacognition and Learning (2019) and Nancy Perry, Metacognition and Learning (2019). This special issue constitutes an important step towards an understanding of the interplay of self-regulation with child and parent characteristics in early childhood.